Auto-Segmentation Analysis Of EMG Signal For Lifting Muscle Contraction Activities - Shair, Ezreen Farina; Abdullah, Abdul Rahim; Tengku Zawawi , Tengku Nor Shuhada; Ahmad, S.A; Mohamad Saleh, Saleha (Penerbit Universiti, UTeM, 2016)
-